Pola Operasi Penggilingan Padi Pasca Program Revitalisasi PPK Sumatera Barat - Jorie, Donna Gracia; Fitriana, Widya; Martius, Endry (Jurnal Ilmiah Muqoddimah: Jurnal Ilmu Sosial, Politik dan Hummaniora, 2026)
The Revitalization of Small Rice Mills (PPK) is a strategic program of the West Sumatra Provincial Government aimed at improving the efficiency of the rice supply chain and strengthening farmers’ bargaining position. This study aims to describe the operational patterns of rice milling following the implementation of the PPK Revitalization Program. The research employed a survey within a case study design using a qualitative descriptive approach involving two farmer groups in Tanah Datar Regency and Pesisir Selatan Regency. The results show two emerging operational patterns: (1) a Vertical and Horizontal Integration Operational Pattern in farmer-group-owned PPK (Tanjung Mutiara Farmer Group), where upstream-to-downstream activities are integrated within the farmer group along with cooperation across business units; and (2) a Limited Vertical Integration Operational Pattern in PPK owned by individual farmer group members (Karakek Indah Farmer Group), where integration occurs because one stage of production is linked to the farmer group with limited authority. The PPK revitalization program has led to changes in stakeholder involvement, a shift in product form from unhusked paddy to rice, and expanded marketing areas reaching other provinces.